Sintesis Membran Ultrafiltrasi Polisulfon Untuk Pengolahan Limbah Cair Mall : Variasi Komposisi Polisulfon - Amin Fitra; Jhon Armedi Pinem; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Membrane is a selective and semipermeable layer that lies between two phases, namely feed phase and permeate phase. Membrane synthesis using polysulfone with phase inversion method. The purpose of this research were to make membranes of polysulfone for waste water treatment mall with 11%, 13%, 15%, and 17% by weight of polysulfone, operating pressure of 1, 2, and 3 bars. This research produed porous membrane. Based on characterization of membrane permeability, selectivity, and porous statistic showed that membrane polysulfone were proven as membrane ultrafiltration.Keywords : phase inversion, membrane, waste water treatment mall, ultrafiltration